Analisis Faktor-faktor yang Mempengaruhi Pendapatan Nelayan di Desa Sanur Kaja Kecamatan Denpasar Selatan - BALMED, AMARA PRISILYA; SUSRUSA, KETUT BUDI; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Analysis of Factors Affecting Fishermen's Income in Sanur Kaja Village, South Denpasar District The level of fishermen's welfare is largely determined by the catch or what is commonly referred to as the production of the catch. The number of catches directly also affects the amount of income received so that fishermen are able to meet their daily needs. This research was conducted with the aim of analyzing and knowing what factors affect the income of fishermen in Sanur Kaja Village, South Denpasar District, which is measured by their average income. In this study, there is one dependent variable, namely fishermen's income (Y) and the independent variable, namely capital (X1), labor (X2), technology (X3). This study was analyzed using multiple linear regression analysis. The number of samples is 40 people with the census method. The data collection technique was carried out by structured and in-depth interviews, observation and questionnaires. The results of the study found that the variables of capital, labor, and technology used had a significant effect on fishermen's income, which means that every additional capital, labor, and technology used, the income of fishermen in Sanur Kaja Village, South Denpasar District will also increase.